The Effect of Parent Psychological Distress on Child Hyperactivity/Inattention During the COVID-19 Lockdown: Testing the Mediation of Parent Verbal Hostility and Child Emotional Symptoms - Marchetti, Daniela; Fontanesi, Lilybeth; Di Giandomenico, Serena; Mazza, Cristina; Roma, Paolo; Verrocchio, Maria Cristina (Frontiers in Psychology, 2020)
The COVID-19 health crisis is strongly affecting the psychological well-being of the general population. According to the very recent literature, the imposed lockdown and social distancing measures have generated a series of negative outcomes, including fear of the future, anxiety, and somatization symptoms. Few studies have investigated the impact of the COVID-19 pandemic on the well-being of parents and children, and still fewer studies have assessed the relationship between parents’ and children’s psychological health. The present study aimed at understanding the effect of parents’ psychological distress and verbal aggression on children’s behavioral and emotional symptoms during the COVID-19 lockdown. Using an online survey administered in the first weeks of the lockdown in Italy, we explored the mediating effects of parent verbal hostility and child emotional symptoms on the relationship between parent distress and child hyperactivity/inattention in a sample of 878 Italian parents (87.4% mothers; Mage = 40.58). Two hypotheses were proposed: (1) parent distress would significantly predict child hyperactivity/inattention; and (2) parent verbal hostility and child emotional symptoms would mediate the association between parent distress and child hyperactivity/inattention. The serial mediated model confirmed both hypotheses, suggesting that higher rates of psychological distress in parents were associated with higher levels of hyperactivity/inattention in children. Parent verbal hostility and child emotional problems were also found to positively mediate this relation. Our results may be used to improve socio-psychological interventions in the general population in the near future. They may also contribute to the clinical definition of therapeutic paths for parents and families.